Banalitas Informasi Jurnalisme Infotainment dan Dampaknya terhadap Penonton - Tri Hastuti Nur R; Fajar Junaedi (Program Studi Ilmu Komunikasi, 2010)
This article is based on a research of information banality in television infotainment programs and the effects to the audience. The research uses the ethnography of communication method at the level of decoding and encoding process. It results that in infotainment production process, TV station often disregards the journalism ethic principles. This statement is proved by -for example - many cases of some celebrities sue the infotainment crew because the celebs feel suffered by infotainment news. The infotainment news packaging in infotainment program also shows a phenomenon called “market-driven journalism”, which breaks the “cover both side